Peter Božič and the question of the authentic theatrical avant-garde in Slovenia in the second half of the 20th century - Troha, Gašper (Amfiteater (Ljubljana), 2025)
Peter Božič was a Slovenian playwright whose most important plays were written at the beginning of his career, between 1955 and 1961. This writing is strongly connected to the then-avant-garde theatre Oder 57 (Stage 57), which presented opposition to the then prevailing style of socialist realism in Yugoslavia. Young dramatists, directors and actors sought new ways of expression, leaning on existentialist philosophy, Artaud's theatre and modernist literature. However, when asked about the influences on his work, Božič replied: “When I was writing Človek v šipi (Man in the Window – his first play), I was leaning on my own life experience, not knowing that this form was in fact avant-garde theatre. Only later, when I first saw Ionesco on stage, did I realise, this is it.” When he later explains the influence of Beckett and Ionesco on his plays, he admits that they were important to him in “the cultural sense. However, when it comes to my plays’ content, the war had a much stronger influence. During the war, all my values were shattered to pieces.” How authentic was the development of the avant-garde theatre of Peter Božič on the European periphery? To what extent can it be compared to the works of Beckett and Ionesco? The author analyses this relationship between the centre in France and the periphery in Slovenia by comparing the early plays of Peter Božič and the works of Beckett and Ionesco that Božič saw or read in Slovenia – The Bald Soprano and The Lesson by Ionesco and Waiting for Godot and Endgame by Beckett.
Keywords: avantgarda; avant-garde; drama absurda; Eugene Ionesco; Peter Božič; Samuel Beckett; theatre of the absurd